Hipnoterapi Dengan Part Therapy Untuk Penurunan Perilaku Merokok - Giyati; Kamsih Astuti; Siti Noor Fatmah (LPPM Universitas Muhammadiyah Riau, 2019)
Smoking becomes big problems in the society. A smoker finds some difficulties in trying to quit smoking. This is because of the inner conflicts between making decision of quitting or continuing smoking. Therefore, it is necessary to look for interventions to solve these problems. This study aims to determine the effect of hypnotherapy with part therapy to decrease smoking behavior. This study was conducted on 2 smokers. The research design is single case experiment design with A-B-A-B-A design. Data analysis used simple descriptive test by presenting data using graph and histogram. The results showed that there are some differences in smoking behavior before and after intervention. The intention of smoking of MFH before intervention is more than 15 cigarettes per day (weight category) becomes medium category (4-15 sticks per day) after the interventions. Whereas, the NK before the interventions that is in medium category (4-15 cigarettes per day) becomes mild category (1-4 stems per day) after the intervention of smoking places. The places that are commonly used by MFH are private rooms, campus and food stalls, while NK used food stalls as the place to smoke. The smoking situation for MFH and NK is when they are hanging out with friends. The functions of smoking for MFH are for adding pleasure, pleasing feeling, and reducing anger and anxiety while the function of smoking for NK is for adding pleasure. After doing hypnotherapy with part therapy, the intention of smoking, smoking place, smoking situation and the function of smoking has decreased. However, in those factors the subject still do smoking behavior but in light intention. The physical and psychological changes after intervention of MFH are the subjects feel freshness and good breathing. MFH had self-awareness, more strong desire, and more healthy life with new pattern to stop smoking, while NK becomes fresher, good feeling, happy, and breathe smoothly, can refuse a friend's invitation to smoke, and has more to strength to quit smoking. Based on the research results, it can be concluded that there is influence of hypnotherapy with part therapy in decreasing smoking behavior. Smoking behavior after intervention was lower than before intervention